Modulating the Electronic and Solid‐State Structure of Organic Semiconductors by Site‐Specific Substitution: The Case of Tetrafluoropentacenes. Issue 15 (25th February 2020) - Geiger, Thomas; Schundelmeier, Simon; Hummel, Thorsten; Ströbele, Markus; Leis, Wolfgang; Seitz, Michael; Zeiser, Clemens; Moretti, Luca; Maiuri, Margherita; Cerullo, Giulio; Broch, Katharina; Vahland, Jörn; et al.
Abstract: The properties as well as solid‐state structures, singlet fission, and organic field‐effect transistor (OFET) performance of three tetrafluoropentacenes (1, 4, 8, 11: 10, 1, 4, 9, 10: 11, 2, 3, 9, 10: 12 ) are compared herein. The novel compounds 10 and 11 were synthesized in high purity from the corresponding 6, 13‐etheno‐bridged precursors by reaction with dimethyl 1, 2, 4, 5‐tetrazine‐3, 6‐dicarboxylate at elevated temperatures. Although most of the molecular properties of the compounds are similar, their chemical reactivity and crystal structures differ considerably. Isomer 10 undergoes the orbital symmetry forbidden thermal [4+4] dimerization, whereas 11 and 12 are much less reactive. The isomers 11 and 12 crystallize in a herringbone motif, but 10 prefers π–π stacking. Although the energy of the first electric dipole‐allowed optical transition varies only within 370 cm −1 (0.05 eV) for the neutral compounds, this amounts to roughly 1600 cm −1 (0.20 eV) for radical cations and 1300 cm −1 (0.16 eV) for dications. Transient spectroscopy of films of 11 and 12 reveals singlet‐fission time constants (91±11, 73±3 fs, respectively) that are shorter than for pentacene (112±9 fs). OFET devices constructed from 11 and 12 show close to ideal thin‐film transistor (TFT) characteristics with electron mobilities of 2×10 −3 and 6×10 −2 cm 2 V −1 s −1, respectively. Abstract : Under the influence of fluorine : The (photo‐)physical and chemical properties of tetrafluoropentacene regioisomers are altered considerably in dependence of the substitution pattern. The variation of the fluorination degree and pattern of pentacenes provides a useful model for gaining detailed insight into forces that control crystallization and for studying the structure–property relationships of these organic semiconductors.